(untitled) (Raparin Journal of Humanities (RJH), 2024)
In our study we discussed the ability of administrative decision to establish obligation as an independent source of obligation or considered as an application of the unilateral will. We found that when the administration commits itself in the cases prescribed by law from the applications of unilateral will, the administrative decision is a source of obligation as an application of unilateral will and not as a direct source of obligation. However, it’s possible for administration to commit itself through its decision other than those cases prescribed by law from the applications of unilateral will, also in it is decisions, administration not only imposes obligation on itself but may also impose obligations on those who deal with administration. Therefore, the administrative decision, also in it is form constitutes a unilateral will application, would in such cases be a direct source of obligation rather than an application of unilateral will. The limited application of the administrative decision establishing the obligation according to the concept contained in the jurisprudence of civil law does not reduce the role of the administrative decision as source of the obligation, The administrative decision within such limited applications is a general source of obligation, as are other sources of obligation, because the applications of each of the sources of obligation mentioned in civil regulations are limited, and the applications of the administrative decision that creates the obligation are more when compared to some of these sources, such as individual will and gain without a legal reason